Análise do IDH do Brasil, de suas regiões e de outros países: um enfoque comparativo - Toni Junior, Claudio Noel de (2010)
This text is going to show many ways that compose the IDH until the year of 2007 that they are going to be talked the analysis the development for the development from the countries for the Program of the Union Nation to the development from the Union Nation Organizations PNUD ONU. The first chapter is going to show the definition of IDH its particulars, methods of calculus and its structurations beyond the observation from three ways that componde the indicator in the actuality income per capita, health, and education. For helping in your understand, we are going to include the index of Gini to help us in our analysis. In the second chapter, we are going to do an analysis commented and compared of the Brazilian s IDH in terms of inner regions for that we could understand the discrepancies that there are in the same country being utile when analysis the Brazilian s IDH in general forms. In the third and forth chapter we are going to do the analysis of IDH among the nations, showing the evolution and the retreat of each country got along the years, their deficiencies in determinates sectors like social or economics, the characteristics and the reasons of the countries show us the variables of optimization of the quality of live in remains from nations that hale index medium and others in precarious situations. We are going to analyses the divergences that there we are among many region in the globe where we are going to do the calculus between the sub-regions, for examples we are going to analyses the IDH of Emirates Arabs, Africa, Subssariana, Latin America inside others. In the forth chapter we are going to show the IDH in 2007 with the brief report of the IDH the 2009 that gets their relatives facts to indicaters of 2006 the insert of Brazil in context latin and world-wide the observation of first placing, to the last, and the motives that took these countries to get these classification. In the fifth chapter we are going to show the criticism that are done in the index at the meaning of the same not portray with the total real fidelity condition of development that a nation meet and the possible inclusion of others variables that could do the IDH the index much precise. Also be boarding the difficulties of methodologies that exist in case of others variables go in to the index. At the of this text we are going to reunite the annexed of some interviews with professors, or specialist in the field of socialeconomics about the problematization of the index.